PATHOMORPHOLOGICAL CHANGES IN ORGANS WITH A COMBINATION OF NEW CARONAVIRAL INFECTION (COVID-19) AND PNEUMOCONIOSIS IN WORKERS OF THE COAL INDUSTRY OF KUZBASS - Олег Иванович Бондарев; Дмитрий Евгеньевич Семенов; Галина Анатольевна Лапий; Мария Сергеевна Бугаева; Анастасия Сергеевна Казицкая (Медицина в Кузбассе, 2020)
Objective – on the basis of pathomorphological data, to determine the pathogenetic significance in the thanatogenesis of a new coronavirus infection (COVID-19) in combination with pneumoconiosis in coal workers.